2012
DOI: 10.4103/0972-5229.99114
|View full text |Cite
|
Sign up to set email alerts
|

Admission source and mortality in a pediatric intensive care unit

Abstract: Background and Aims:Studies carried out in different countries have shown that source of patient admission in Intensive Care Units (ICUs) is associated to death. Patients admitted from wards show a greater ICU mortality. The aim of the present study was to investigate the association between admission source and outcome in a Pediatric Intensive Care Unit (PICU).Materials and Methods:We studied all PICU admissions that took place between January 2002 and December 2005 in a tertiary hospital in Brazil. The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 15 publications
5
43
1
1
Order By: Relevance
“…This may be due to the wide age (2 weeks–18 years) distribution of patients admitted to our ICU. However, the age distribution of ICU admission of which, the majority were under five (62.5%), was similar to studies done in India, 53–72.4% were under five [913]. The preponderance of male sex (53.8%) was similar to study done in Ethiopia − 54.7% [6] and Brazil − 55.2% [13], but somehow lower than studies done in India, Nepal, and Greek (54–61.1%) [912, 14].…”
Section: Discussionsupporting
confidence: 81%
“…This may be due to the wide age (2 weeks–18 years) distribution of patients admitted to our ICU. However, the age distribution of ICU admission of which, the majority were under five (62.5%), was similar to studies done in India, 53–72.4% were under five [913]. The preponderance of male sex (53.8%) was similar to study done in Ethiopia − 54.7% [6] and Brazil − 55.2% [13], but somehow lower than studies done in India, Nepal, and Greek (54–61.1%) [912, 14].…”
Section: Discussionsupporting
confidence: 81%
“…1 Although the total number of hospital beds in the United States decreased by 26.4% from the year 1985 to 2000; the ICU beds increased by 26.2% during the same period. 2 As a fact, we know little on the exact causes of death and the impact of risk factors that may complicate the course of critical illness irrespective of the underlying disease.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, PIM2 predicted mortality was 6.5%. 21 In Iran, a prospective cohort study to validate PIM2 performance in a tertiary hospital in Tehran, the observed mortalities among children admitted to the PICU reached 15%, while PIM2 predicted mortality was 8.3%, SMR is 1.8 (95% CI 1.28-2.46). 22 Of the limitations of the study is that it is hospital-based, thus the observed mortality rate of 8.4% cannot be generalized to represent children's mortalities admitted to PICUs all over Egypt.…”
Section: Discussionmentioning
confidence: 98%